Mobile encounters : artists' mobility between Ireland and Britain and the development of performance, video and multimedia practices (1975 - 1999) - Fitzgibbon, Jennifer (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2014)
This thesis investigates the encounter between Irish and British time-based artists between 1975 and 1999. Taking artists’ mobility as a primary subject of this investigation, the research considers important policy milestones, people, events, organisations and critical attitudes that contributed to how artists formed links and relationships with other artists located abroad. Focussing on Irish time-based art, taken in the context of this thesis to refer to performance, film, video and multimedia outputs, the research presents a chronological analysis of relevant issues in areas of provision, artists’ practices and critical reception during the stated time-frame.
Keywords: History Of Art, Ph.D.; Ph.D. Trinity College Dublin